2017
DOI: 10.1590/1983-21252017v30n330rc
|View full text |Cite
|
Sign up to set email alerts
|

CHEMICAL COMPOSITION AND TOXICITY OF CITRUS ESSENTIAL OILS ON Dysmicoccus brevipes (HEMIPTERA: PSEUDOCOCCIDAE)

Abstract: -The insect Dysmicoccus brevipes (Hemiptera: Pseudococcidae) has been reported as an important pest for several crops, especially coffee. The citrus essential oils can be obtained as by-products of the citrus-processing industry and have been tested as an alternative to control different insect groups. Therefore, the objective of this work was to determine the chemical composition and evaluate the toxicity of commercial sweet orange (Citrus sinensis), bitter orange (Citrus aurantium) and Sicilian lemon (Citrus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 14 publications
0
9
0
3
Order By: Relevance
“…It is important to point out that γ‐terpinene was not identified in any of the oils investigated in the present study. However, this monoterpene was the major constituent of the peel oil of the mandarin orange ( C. reticulata ) from elsewhere in Brazil (Badawy et al, ; Martins et al, ) as well as China (Tao et al, ) and Egypt (Mohamed & Abdelgaleil, ). γ‐Terpinene has also been found to be the major component of the peel oil of the key lime ( C. aurantiifolia ) from Italy (Costa et al, ), Egypt (Badawy & Abdelgaleil, ) and Brazil (Amorim et al, ) as well as the lemon ( C. limon ) from India (Jain & Sharma, ; Semwal, Semwal, Mishra, & Semwal, ), Iran (Ghoorchibeigi et al, ), Brazil (Amorim et al, ) and Algeria (Djenane, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to point out that γ‐terpinene was not identified in any of the oils investigated in the present study. However, this monoterpene was the major constituent of the peel oil of the mandarin orange ( C. reticulata ) from elsewhere in Brazil (Badawy et al, ; Martins et al, ) as well as China (Tao et al, ) and Egypt (Mohamed & Abdelgaleil, ). γ‐Terpinene has also been found to be the major component of the peel oil of the key lime ( C. aurantiifolia ) from Italy (Costa et al, ), Egypt (Badawy & Abdelgaleil, ) and Brazil (Amorim et al, ) as well as the lemon ( C. limon ) from India (Jain & Sharma, ; Semwal, Semwal, Mishra, & Semwal, ), Iran (Ghoorchibeigi et al, ), Brazil (Amorim et al, ) and Algeria (Djenane, ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies describing the biological properties of Citrus oils highlight their potential for the control of different arthropods. Regarding the species investigated in the present study, the literature offers reports on the effect of the EO from Citrus limon against pests of interest to veterinary medicine (Aboelhadid, Mahrous, Hashem, Abdel-Kafy, & Miller, 2016), human medicine (Selvakumar, Gokulakrishnan, Elanchezhiyan, & Deepa, 2015), agriculture (Martins, Zago, Costa, Araujo Junior, & Carvalho, 2017) and grain storage (Karabörklü, Ayvaz, Yilmaz, & Akbulut, 2011). The EO from…”
Section: Fumigant and Residual Contact Bioassaymentioning
confidence: 99%
“…Insecticides, such as soaps, tobacco extract, mercury, sulfur, and oils have been recommended in field applications . It has been reported that Sicilian lemon oil was highly effective to control PPM …”
Section: Discussionmentioning
confidence: 99%
“…8 It has been reported that Sicilian lemon oil was highly effective to control PPM. 82 Secondly, the discovery of natural predators of PPM and GPM can be an effective approach to reducing their spread. Entomopathogenic nematodes (Heterorhabdtis indica Poliner, Karunakar & David) have great potential to control PPM due to their high mortality rates upon PPM infection.…”
Section: Discussionmentioning
confidence: 99%
“…Menurut Nurhaifah dan Tri (2015) semakin rendah nilai LC50 suatu insektisida alami maka, semakin baik pula efektivitas insektisida tersebut karena dengan jumlah bahan baku yang sedikit dapat menghasilkan daya racun yang tinggi. Martin et al (2017) nilai LC 50 kulit jeruk manis lebih tinggi dibandingkan dengan kulit jeruk lemon. Dalam penelitiannya juga dijelaskan bahwa aktivitas insektisida dari ekstrak kulit jeruk lebih didominasi oleh senyawa limonen dan linalool.…”
Section: Nilai Lc 50unclassified